MANAJEMEN KURIKULUM MERDEKA BELAJAR DI SMA UNGGULAN AL-AZHAR MEDAN - Matondang, Khoiruddin; Nurhayati, Nurhayati; Saragih, Risna MIra Bella; Kusyani, Diah (FKIP Universitas Al Washliyah Medan, 2025)
Education in Indonesia is undergoing transformation through the implementation of the Independent Learning Curriculum which aims to provide flexibility in learning, improve 21st century competencies, and integrate local values. This research aims to understand the management of the Independent Learning Curriculum at Al-Azhar Superior High School Medan, including planning, implementation, and evaluation strategies. The research uses a qualitative approach with the type of case study, involving school principals, teachers, students, and education staff as research subjects. Data were collected through in-depth interviews, participatory observations, documentation studies, and qualitative analysis of the Miles and Huberman model. The results of the study show that Al-Azhar Medan High School uses a student needs-based approach with a focus on developing individual talents, interests, and abilities through technology-based learning methods and special religious programs. The implementation of the curriculum includes project-based learning to improve students' critical thinking skills, with the support of modern infrastructure. Curriculum evaluation is carried out collaboratively, involving teachers as direct evaluators and students as feedback givers through reflections and evaluation-based projects. This study concludes that the management of the Independent Learning Curriculum at Al-Azhar Medan High School has created an innovative learning environment, relevant to the demands of the 21st century, and centered on the development of students' potential holistically.